Effects of Magnesium Forms on the Magnesium Balance and Jejunal Transporters in Healthy Rats - Er, Besir (Korean Soc Food Science Nutrition, 2024)
Magnesium (Mg) is a mineral necessary for many biological activities in mammals. Here, we compared the effect of two Mg compounds [Mg picolinate (MgPic) to Mg oxide (MgO)] on Mg bioavailability and intestinal Mg and calcium transporter protein levels. Three groups of 21 male Wistar-Albino rats were randomly allocated and fed a standard diet (control) or a 500 mg/kg Mg-supplemented (MgPic or MgO) diet for 8 weeks. The serum and liver Mg levels, Mg absorptivity, and retentivity were augmented in the MgPic group compared with the MgO group (P<0.05). Only MgPic supplementation elevated the expression of the genes encoding CLDN2, CLDN15, CNNM4, NCX1, PMCA1b, NCX2, and Calbindin-D9k in the jejunum by 1.59, 1.58, 1.70, 1.82, 2.02, 2.03, and 2.31 fold, respectively (P<0.05). Compared to the MgO-fed rats, MgPic rats had higher expression of the genes encoding NCX1, NCX2, PMCA1b, and Calbindin-D9k in the jejunum by 1.43, 1.72, 1.54, and 1.69 fold, respectively (P<0.01). These results suggest that MgPic increases Mg absorptivity and retentivity more than Mg bioavailability. In addition, MgPic can improve the paracellular and transcellular cationic mineral transport process. Thus, Mg deficiency disorders might be alleviated by MgPic more effectively than MgO.
Keywords: bioavailability; biological transport; dietary supplements; magnesium oxide; picolinic acid